Neuroepidemiology study of headache in the region of Jammu of north Indian population: A cross-sectional study - Sudershan, Amrit; Pushap, Agar Chander; Younis, Mohd; Sudershan, Srishty; Bhagat, Sheetal; Kumar, Hardeep; Panjalyia, Rakesh K.; Kumar, Parvinder (Frontiers in Neurology, 2023)
Background Headache disorders now represent a major public health problem globally. It is more prevalent in developing countries with the rising trends of headache disorders observed in young adults affecting their quality of life negatively. Very little information is available on the epidemiology of headache disorders in the Jammu Division of the north Indian population. Aim The aim of the present study was to find out the prevalence of headache and its two major types, i.e., migraine and tension-type headache (TTH), in the population of the Jammu Division. Methods The present study was conducted in two phases: (Phase I: face-to-face interview and Phase II: E-based sampling) and the sufferers of headaches were incorporated into the study based on the International Classification of Headache Disorder-3 (ICHD-3) criteria for a representative sample. Frequency distribution and mean ± standard deviation were used in descriptive statistics to describe the data sets, while a t-test, chi-square test, multiple logistic regression, and prevalence ratio were used in inferential statistics. Results In the present study, a total of 3,148 patients were recruited, with an overall prevalence of headache of 53.84%, with a majority of females (38.18%) over males (15.66%). As regards the type of headache, migraine was found to be of the more prevalent (33.25%) type than the TTH (20.58%). Females suffering from migraine showed the highest prevalence (25.28%), in contrast to females suffering from the TTH (12.89%). Sociodemographic variables, such as gender [female; AOR = 2.46, 95% CI (2.12–2.85), p-value < 0.0001] and marital status [married; AOR: 1.46, 95% CI (1.11–1.92) p-value = 0.006], showed a significant association with the headache. Conclusion The present study shows that the prevalence of headache is high in the Jammu Division of Jammu and Kashmir (J&K) India, with migraine being the highly prevalent type.